Rates of Intrauterine Device Insertion in Postpartum or Postabortion Women [13O]. (May 2016) - McCarthy, H. Catherine; Howard, Brandon; Eid, Sherrine; Strachan, Gordon; Tang, Boxiong
Abstract : INTRODUCTION: In 2011, the American Congress of Obstetricians and Gynecologists recommended intrauterine device (IUD) insertion immediately post-partum (within 10 minutes after placental delivery) or post-abortion as favorable, safe, and effective for most patients in this setting. METHODS: Truven Health MarketScan database is a large claims database containing data from patients enrolled in employer and commercial health plans, including a sampling of Medicaid plans. Truven's Treatment Pathways 3.0 tool was used to retrospectively examine IUD insertion rates in post-partum or post-abortion women from 2011–2014. The proportion of patients undergoing IUD insertion in less than 1 day, or within 1, 4, 6, or 8 weeks post-partum or post-abortion were analyzed to estimate trends over time per insertion using R 2 to test the model's strength to explain variability. RESULTS: From 2011–2014, 2, 696, 176 women were post-partum or post-abortion. Of those, 2.32% had an IUD inserted within 8 weeks post-partum or post-abortion, 0.72% within 6 weeks, 0.24% within 4 weeks, 0.11% within 1 week, and 0.09% in less than 1 day. Regardless of timing, there was a steady increase in insertion rates over the years. IUD insertion rates within 8 weeks post-partum or post-abortion increased from 1.9% in 2011 to 2.4% in 2014 (y=0.162x+1.72, R 2 =0.981). CONCLUSION: Although IUD insertion among women post-partum or post-abortion has increased over the years, few women received an IUD immediately post-partum or post-abortion, despite updated recommendations. Additional research is needed to determine the reasons for low rates of IUD insertions immediately post-partum and post-abortion. Support: Teva Pharmaceuticals.